Enhancing Students' Vocabulary through Interactive Word Wall Learning at SMP Yanbu'ul Hikmah - Samsul Arifin; Sulistyaningsih (Didaktika: Jurnal Kependidikan, 2024)
Possessing a sufficient vocabulary in English might motivate someone to write and converse in the language. Therefore, it is thought that vocabulary mastering is crucial for both the process of learning a language and the growth of a person's ability to learn a language. The number and quality of a person's vocabulary determine the level of their language abilities. Action research is the desired and appropriate research design for this study. The findings indicate that the efforts made by the researchers and their partners to use word wall learning materials to help third-grade SMP YANBUUL HIKMAH better understand English vocabulary has increased. Third-grade students agreed that using word wall media to study English will help them become more proficient in the vocabulary learning process is considered successful when there is a positive change in the student's overall self, or at least in part, 75% of the time. This is demonstrated by the learning outcomes. Therefore, it can be said that class III pupils'' mastery of the English vocabulary can be enhanced by using word wall media.